Relationship between human resource management practices and organizational performance: the moderating role of interfirm collaboration and environment of Malaysian research and development (R&D) organizations / Zurina Adnan - Adnan, Zurina (Institute of Graduate Studies, UiTM, 2014)
Since 1996, the Research and Development (R&D) sector in Malaysia has received greater policy attention than before. Despite fiscal and non-fiscal incentives provided to support the growth of this sector, the level of R&D measured in terms of R&D outputs (i.e. number of patent) is still dismal which is mirrored in the overall performance of local R&D companies. Many studies have investigated factors which influence the performance of organizations. The present study attempts to examine the relationship between human resource management (HRM) practices and organizational performance of R&D firms based on contingency theory and resource based view. The moderating role of interfirm collaboration and environment on the relationship between HRM practices and organizational performance are also studied.